A 2d kinematic analysis of front kick speed in pencak silat athletes from south lampung regency - Inosen Lingsir Maghribi; Bagus Aryatama; Burhaan Shodiq; Boy Sembaba Tarigan; Imam Safei; Inosen Lingsir Maghribi; Bagus Aryatama; Burhaan Shodiq; Boy Sembaba Tarigan; Imam Safei (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2026)
This study aimed to describe the kinematic characteristics of front kick speed in regional level Pencak Silat athletes from South Lampung Regency preparing for the 10th Lampung Provincial Sports Week (PORPROV X) in 2026. A quantitative descriptive approach was employed involving ten athletes (six males and four females) who were actively participating in a centralized training program. Front kick performance was recorded using a high-speed Fujifilm X-T4 camera at 240 frames per second with a 50 mm focal length lens to minimize perspective distortion. The recorded videos were analyzed using Kinovea 2025.1.1 software through two-dimensional kinematic analysis. The measured variables included kick displacement, execution time, and average kick speed. The results showed that male athletes achieved higher average front kick speeds (2.75 m/s) than female athletes (2.33 m/s), primarily due to shorter execution times rather than greater displacement. Overall, performance was characterized by adequate movement range but lower temporal efficiency compared to values reported in elite athletes, indicating that execution time is a key determinant of front kick speed at the regional level. This study contributes to the biomechanics of Pencak Silat by providing empirical kinematic data at the provincial level and identifying execution time as a primary performance-limiting factor. These findings offer a biomechanical basis for targeted training interventions focusing on neuromuscular coordination, explosive strength, and movement acceleration. It can be concluded that improving temporal efficiency is critical to enhancing front kick performance. Future studies should incorporate larger samples and three-dimensional analysis for a more comprehensive understanding.